Towards Usury-Free Finance in Land Pawning: Evaluating Carter and Angkat-Bloe Contracts - Siregar, Ahmad Sholihin; Ainiah, Ainiah; Daud, Zakiul Fuady Muhammad (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2024)
Pawn transactions fall under tabarru' contracts, which prohibit the accrual of profit, as such gains are categorized as usury and are forbidden in Islam. In situations where pawn contracts are prevalent, Islam offers alternatives to avoid usury. In the Kuta Makmur community of Aceh, the carter and angkat-bloe contracts are seen as viable alternatives to land pawn contracts. This study aims to analyze the carter and angkat-bloe contracts among the community and analyze their permissibility from an Islamic economic perspective. This research employs a descriptive qualitative approach, utilizing observation and interviews for data collection. The findings reveal that the carter contract is analogous to lease agreements and, therefore, is permissible as an alternative to avoid usury. However, the angkat-bloe contract shares similarities with the bai' al-wafa' contract, the legality of which remains debated among Islamic jurists (Fukaha). The permissibility of the angkat-bloe contract depends on its substance and the intention behind its execution. This study suggests that the carter contract could be legitimized by the National Sharia Council as a solution for individuals facing economic challenges, while the angkat- bloe contract requires further scrutiny based on the intentions and substance of its practice.========================================================================================================ABSTRAK - Menuju Keuangan Bebas Riba dalam Gadai Tanah: Evaluasi Akad ‘Carter’ dan ‘Angkat-Bloe’. Gadai merupakan bagian dari akad tabarru’ yang tidak memperbolehkan pengambilan keuntungan, karena manfaat tersebut masuk dalam kategori riba yang diharamkan dalam Islam. Di sisi lain, Islam memberikan solusi alternatif untuk menghindari riba dalam akad gadai, seperti praktik akad ‘carter’ dan ‘angkat-bloe’ dalam masyarakat Kuta Makmur, Aceh, yang disinyalir sebagai alternatif untuk menghindari riba. Penelitian ini bertujuan untuk menganalisis praktik ‘carter’ dan ‘angkat-bloe’ dalam komunitas tersebut serta menganalisisnya dari perspektif ekonomi syariah. Hasil penelitian menunjukkan bahwa akad ‘carter’ memiliki kemiripan dengan akad sewa-menyewa dari segi substansinya, sehingga akad ‘carter’ dibolehkan dan bisa menjadi alternatif untuk menghindari riba. Sementara akad ‘angkat-bloe’ mempunyai kemiripan dengan akad bai’ al-wafa’ yang hukumnya masih diperdebatkan Fukaha. Berdasarkan argumen Fukaha, kajian ini menyimpulkan kebolehan akad bai’ al-wafa’ serta akad angkat jual yang mirip dengannya sangat tergantung pada subtansi dan niat dalam pelaksanaannya. Penelitian ini mengusulkan agar akad ‘carter’ dapat dilegalkan oleh Dewan Syariah Nasional sebagai solusi bagi masyarakat yang mengalami kesulitan ekonomi, sedangkan akad ‘angkat-bloe’ memerlukan kajian lebih lanjut terkait niat dan substansinya.